“Diseño e implementación de un sistema de bombeo de agua, alimentado por un sistema fotovoltaico para riego por goteo en el barrio Rumipamba de Navas- Salcedo” - Sangucho Changoluisa, Jeferson Leonel (2021)
Nowadays, the lack of electricity supply in hard-to-reach places in agricultural areas has caused several problems, one of them being the lack of vital liquid for crops. Therefore, the use of photovoltaic technologies is suitable for obtaining electricity in places of difficult commercialization and distribution. That is why this thesis aims to implement a water pumping system powered by a photovoltaic system for drip irrigation in the neighborhood Rumipamba of Navas Cantón - Salcedo through an experimental and field methodology a technological proposal was made in order to supply alternatively with a pumping system to three greenhouses of kidney tomato whose areas are Greenhouse 1 1 = 3000 2, greenhouse 2 2 = 2000 2, greenhouse 3 3 = 1300 2; which lack of vital liquid, on the other hand, 3 solar panels were used as a fundamental element in the photovoltaic system, 3 batteries were also used as an accumulation system, as well as a charge regulator in charge of the charge and discharge process of the batteries and an inverter of the photovoltaic system which will transform different charge voltages and a ¾ HP pump for the irrigation of all the greenhouses. As a result, the implementation was verified to be working correctly, as the pump start-up was normal with a current of 6 A and a maximum current of 34 A from the panels